Unusual Cystic Variant of Calcifying Epithelial Odontogenic Tumor - Mala Kamboj; Achla Bharti Yadav; Anjali Narwal; Neera J (Shiraz University of Medical Sciences, 2020)
Calcifying epithelial odontogenic tumor (CEOT) is a rare benign odontogenic neoplasm, which is exclusively epithelial in its tissue of origin. Many cases of CEOTs are associated with impacted tooth and simulate dentigerous cyst radiographically. The histologic features of CEOT are unique; however, among its various histologic subtypes, the cystic variant is a rare and less well-understood entity. Our report elucidates a cystic variant of CEOT in the maxilla of a 16-year-old male that presents clinical and radiologic findings conscientious to dentigerous cyst; but histopathological diagnosis came out to be a gold standard in identifying this rare tumor. This case report describes the clinicopathologic features of this rare entity, highlighting the histomorphological findings along with reviewing other reported cases.